2007
DOI: 10.1021/ac0623888
|View full text |Cite
|
Sign up to set email alerts
|

Sampling for Metabolome Analysis of Microorganisms

Abstract: In the present work we investigated the most commonly applied methods used for sampling of microorganisms in the field of metabolomics in order to unravel potential sources of error previously ignored but of utmost importance for accurate metabolome analysis. To broaden the significance of our study, we investigated different Gram-negative and Gram-positive bacteria, i.e., Bacillus subtilis, Corynebacterium glutamicum, Escherichia coli, Gluconobacter oxydans, Pseudomonas putida, and Zymononas mobilis, and anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
330
1
7

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 354 publications
(353 citation statements)
references
References 30 publications
11
330
1
7
Order By: Relevance
“…Table 3 shows that 0.55 μM isoleucine still contributes to more than 30% of the total isoleucine present. In correspondence with our findings also Bolten et al (2007) detected intermediates from the glycolysis, TCA cycle and PPP in the supernatant for some bacterial species.…”
Section: Metabolite Measurements In Broth and Supernatantsupporting
confidence: 92%
See 3 more Smart Citations
“…Table 3 shows that 0.55 μM isoleucine still contributes to more than 30% of the total isoleucine present. In correspondence with our findings also Bolten et al (2007) detected intermediates from the glycolysis, TCA cycle and PPP in the supernatant for some bacterial species.…”
Section: Metabolite Measurements In Broth and Supernatantsupporting
confidence: 92%
“…It has been shown that in bacterial cultures significant amounts of several central metabolites and amino acids are present in the culture filtrate (Bolten et al, 2007). These authors also showed that the applied filtration procedure could result in additional leakage of metabolites from the cells.…”
Section: Separation Of Cells and Supernatantmentioning
confidence: 94%
See 2 more Smart Citations
“…Dynamic models are also needed for dynamic labeling experiments for flux analysis as has been shown for E. coli [81]. The current progress in method development for metabolomics of C. glutamicum will surely stimulate the future generation of dynamic models for such organisms by providing extended data sets on intracellular metabolite concentrations required to derive in vivo kinetics [82][83][84][85]. For many years, dynamic macroscopic models have been used to describe dynamic phenomena of growth and production and derive control or feeding strategies for optimized bioprocesses.…”
Section: Dynamic Modeling Approachesmentioning
confidence: 99%